A light-detecting Ru(II)/Si heterojunction system involving a binuclear Ru (II) complex with pyridine-2,6-diimine (pydim) ligand - Koc, Muemin Mehmet; Dayan, Osman; Dere, Aysegul; Cetinkaya, Bekir; Coskun, Burhan; Yakuphanoğlu, Fahrettin (Springer, 2024)
A meticulously detailed chemical procedure was employed to synthesize the Ru (II)-containing pyridine-2,6-diimine (pydim) organometallic complex. The resulting complex was then applied to Al-coated Si wafers using the spin-coating technique, leading to the production of Al/Ru(II) organometallic complex/n-Si/Al photodiodes. The light responsiveness of these photodiodes was demonstrated through the acquisition of I-V and I-t characteristics. Subsequently, essential parameters such as ideality factor, photosensitivity, barrier height, and photoresponse values were evaluated based on the obtained I-V and I-t plots. The calculations yielded ideality factors and barrier heights, resulting in average values of 6.41 and 0.552 eV, respectively. Furthermore, an in-depth analysis of the electrical properties of the diodes was conducted using G-V and C-V assessments, revealing a strong dependence on AC signal frequency. This investigation underscored that the observed frequency-related electrical behaviour is rooted in series resistance and interface states.
Keywords: Ruthenium(Ii) Complexes; Thin-Film; Electrical Characterization; Transfer Hydrogenation; Mononuclear; Photodiode; Layer